2018
DOI: 10.1002/gj.3396
|View full text |Cite
|
Sign up to set email alerts
|

Geochronology and geochemistry ofca. 2.48 Ga granitoid gneisses from theYudongzi Complexin the north‐westernYangtze Block,China

Abstract: The Early Precambrian magmatism in the Archean–Palaeoproterozoic basement Yudongzi Complex is critical for understanding the early crustal formation and evolutionary history of the Yangtze Block in the South China Craton. In this paper, combined zircon UPb geochronological, zircon Hf isotopic, and whole‐rock geochemical studies are carried out on the granitoid gneisses from the Yudongzi Complex, north‐western Yangtze Block. The magmatic zircons from the granitoid gneiss yield a UPb upper intercept age of 2,4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 118 publications
0
1
0
Order By: Relevance
“…Recent research has also reported magmatism at ca. 2.5 Ga in the northern margin of the Yangtze Craton, predominantly exposed in the Douling Complex (Hu et al, 2013; Wu et al, 2014), Yudongzi Complex (Chen et al, 2019; Hui et al, 2019; Zhou et al, 2018), Jiamiao Complex (Tian et al, 2022), Jinpan Complex (Zhang et al, 2022), Xishui Complex (Zhao et al, 2021) and Susong Complex (Wang et al, 2020, 2021). The magmatic rocks of this period are characterised by negative ε Hf (t) values, with corresponding two‐stage Hf model ages (T DM2 ) ranging from 2.7 to 3.7 Ga (Figure 8f).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has also reported magmatism at ca. 2.5 Ga in the northern margin of the Yangtze Craton, predominantly exposed in the Douling Complex (Hu et al, 2013; Wu et al, 2014), Yudongzi Complex (Chen et al, 2019; Hui et al, 2019; Zhou et al, 2018), Jiamiao Complex (Tian et al, 2022), Jinpan Complex (Zhang et al, 2022), Xishui Complex (Zhao et al, 2021) and Susong Complex (Wang et al, 2020, 2021). The magmatic rocks of this period are characterised by negative ε Hf (t) values, with corresponding two‐stage Hf model ages (T DM2 ) ranging from 2.7 to 3.7 Ga (Figure 8f).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, Early Paleoproterozoic (ca. 2.50–2.45 Ga) magmatism and metamorphism have been documented in the northern margin of the Yangtze Craton (Chen et al, 2019, 2023; Hui et al, 2017, 2019; Tian et al, 2022; Wu et al, 2014; Zhang et al, 2022; Zhang, Zheng, et al, 2020; Zhao et al, 2021; Zhou et al, 2018), collectively indicating the development of a subduction system during this period in the northern margin of the Yangtze Craton (Zhang, Zheng, et al, 2020). The arc‐related magmatism in the Early Paleoproterozoic (ca.…”
Section: Discussionmentioning
confidence: 99%
“…Located between the Yangtze Block and the Cathaysia Block, the Jiangnan Orogen is an NNE‐ trending belt extending for 1500 km from north‐eastern Guizhou Province to northern Jiangxi Province and southern Anhui Province (Figure 1a) (Shu et al, 1995, Shu, 2012, Shu et al, 2019; Charvet et al, 1996; Zhao & Cawood, 1999; Zhou et al, 2004; Wang et al, 2007; Wang, Wyman, et al, 2010; Dong et al, 2012; Zhang & Wang, 2019; Dong et al, 2021, 2022). The oldest metamorphic basement rocks in the Yangtze Block are exposed in the Kongling and Yudongzi area, including 3.4–3.2 Ga and 2.9–2.8 Ga TTG gneisses and 3.2 Ga migmatites (Gao, Jie, et al, 2011; Hui et al, 2017; Hui et al, 2019; Li et al, 2014; Qiu et al, 2000; Zhang et al, 2006; Zheng et al, 2006). In the Cathaysia Block, the metamorphic basement rocks have a Neoproterozoic age and are exposed in the north‐eastern part (including southern Zhejiang Province, northern/western Fujian Province and eastern Jiangxi Province), and the south‐western part of the Cathaysia Block (Yu et al, 2008).…”
Section: Geological Background and Samplingmentioning
confidence: 99%